Experimental Investigation of Mechanical and Dynamic Impact Properties of High Strength Cementitious Composite Containing Micro Steel and PP Fibers - Ahmad Dalvand; Ebrahim Sharififard; Fereydoon Omidinasab (Journal of Rehabilitation in Civil Engineering, 2020)
Cementitious composites are one of the most consumed construction materials in the world. The use of cementitious composites is increasing due to their special characteristics. The behavior of high strength cementitious composites is improved by increasing the fiber percentage. In the present paper, the effects of steel microfibers and polypropylene fibers on mechanical properties and impact resistance of high strength cementitious composites are investigated. The percentage of fibers used in the study was 0, 0.5, and 1.5% in seven separate and three combined mix designs. Experiments were carried out on 120 specimens in 10 mix designs. Compressive strength, tensile strength, flexural strength, and dynamic impact tests were carried out on 10 mix designs manufactured in this research. The dynamic impact strength of the disc specimen was investigated by a drop hammer test machine with a capacity of 7500J. After testing the samples, it was shown that using a high percentage of steel and polypropylene fibers reduces the compressive strength and increases tensile strength, flexural strength, and impact strength. The effects of steel microfibers on the reduction of the crush displacement resulting from the dynamic impact were higher than that of polypropylene fibers.